Latent Classes of Substance Use in Adolescent Cannabis Users: Predictors and Subsequent Substance-Related Harm - Fallu, Jean-Sébastien; N.-Brière, Frédéric; Janosz, Michel (Frontiers in Psychiatry, 2014)
Cannabis use is highly prevalent in late adolescence, but not all users experience significant negative consequences. Little information is available to identify the substance use patterns and risk factors of users who are at greater risk of experiencing negative consequences. In this prospective study, we aimed to empirically identify latent classes of substance use in adolescent cannabis users and to examine how these classes relate to antecedent psychosocial predictors and subsequent substance-related outcomes. The sample was recruited from 68 high schools in Quebec and consisted of 1618 participants who reported using cannabis in grade 10. We used latent class analysis (LCA) to empirically identify classes of users based on the age of onset, frequency, and typical quantity of cannabis and other substance use, as well as substance mixing behaviors. We then compared classes in terms of a) socio-demographic and psychosocial predictors in grades 7-8 and b) substance-related consequences in grade 11. Four distinct classes were identified: Late-Light Users (28%); Late-Heavy+Polydrug Users (14%); Early-Moderate Users (33%); Early-Heavy+Polydrug Users (26%). Late-Light Users reported the lowest levels of substance use, while Early-Heavy+Polydrug Users reported the highest levels of substance. Intermediate levels of susbstance use were found in the other two classes. Sex, age, delinquency, peer delinquency, school bonding, parental monitoring, and parental conflict all helped differentiate classes. Class membership predicted substance-related harm, with greater consequences in early- and late-onset heavy using classes. In light of results, in addition to age and sex, screening and intervention for risky cannabis use among adolescents should focus on school bonding in order to target the most risky late-onset adolescents, and on peer delinquency in order to target the most risky early-onset ones.